1999
DOI: 10.2337/diabetes.48.4.675
|View full text |Cite
|
Sign up to set email alerts
|

CaM kinase II: a protein kinase with extraordinary talents germane to insulin exocytosis.

Abstract: CaM kinase II, a multifunctional Ca2+/calmodulin-dependent protein kinase, is expressed in the pancreatic beta-cell and is activated by glucose and other secretagogues in a manner correlating with insulin secretion. It is proposed that the activation of CaM kinase II mediates some of the actions of Ca2+ on the exocytosis of insulin secretory granules. This suggestion is supported by the localization of CaM kinase II to the insulin secretory granule and by the identification of two secretory-relevant proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 0 publications
5
96
0
5
Order By: Relevance
“…It is a multigene family comprised of four distinct classes, α, β, γ, and δ, encoded by four separate genes (see Braun and Schulman, 1995;Easom, 1999 for review of CaM kinases expressed in the b cell). Upon activation in high Ca 2+ levels the enzyme that consists of 8-12 subunits undergoes autophosphorylation and increasing degrees of Ca 2+ oscillation results in increasing number of units being autophosphorylated (Easom, 1999). The phosphorylated enzyme has a greater affinity for calmodulin.…”
Section: Calcium/calmodulin Pathwaymentioning
confidence: 99%
“…It is a multigene family comprised of four distinct classes, α, β, γ, and δ, encoded by four separate genes (see Braun and Schulman, 1995;Easom, 1999 for review of CaM kinases expressed in the b cell). Upon activation in high Ca 2+ levels the enzyme that consists of 8-12 subunits undergoes autophosphorylation and increasing degrees of Ca 2+ oscillation results in increasing number of units being autophosphorylated (Easom, 1999). The phosphorylated enzyme has a greater affinity for calmodulin.…”
Section: Calcium/calmodulin Pathwaymentioning
confidence: 99%
“…lysophospholipids) and Ca 2ϩ -sensitive kinases and phosphatases (e.g. CaMKII␤ and calcineurin) are also proposed to affect these interactions (9,10,25,32). Mechanisms whereby iPLA 2 ␤ participates in glucose-induced rises in ␤-cell cytosolic [Ca 2ϩ ] and insulin secretion are likely to involve Ca 2ϩ -sensitive regulation of modulatory and effector proteins by phosphorylation-dephosphorylation events (9,10), and iPLA 2 ␤ activity is also affected by local [Ca 2ϩ ] increments that relieve its tonic inhibition by Ca 2ϩ /calmodulin (2,8,25).…”
mentioning
confidence: 99%
“…Other studies claim that CaMKII activation is involved in CGE (Markoulaki et al 2003, Sun 2003, Knott et al 2006. As mentioned in the Introduction section, CaMKII, like CaM, is localized at the egg cortex, especially at sites of exocytosis (Shen et al 1998, Easom 1999 and was suggested as a by LCA-biotin (1:100). LCA-biotin was detected by Texas Red Streptavidin (1:1000).…”
Section: Discussionmentioning
confidence: 95%
“…It was hypothesized that CaMKII is required also for CGE and for establishing the block to polyspermy (reviewed by . Although some reports indicate that CaMKII, like CaM, is localized to sites of exocytosis (Shen et al 1998, Easom 1999 and is involved in CGE (Tatone et al 1999, Markoulaki et al 2003); a recent report indicated an abnormal CGE in mouse eggs injected with a constitutively active form of CaMKII (CA-CaMKII; Knott et al 2006).…”
Section: Introductionmentioning
confidence: 99%